2022
DOI: 10.3390/biologics2020010
|View full text |Cite
|
Sign up to set email alerts
|

Abelmoschus esculentus (L.) Moench Pod Extract Revealed Antagonistic Effect against the Synergistic Antidiabetic Activity of Metformin and Acarbose upon Concomitant Administration in Glucose-Induced Hyperglycemic Mice

Abstract: Abelmoschus esculentus (L.) Moench, commonly known as okra, is one of the most widely used vegetable crops currently used for diabetes treatment as well. It is thought that the large amount of soluble dietary fibers present in okra is responsible for the slowing of the absorption of glucose from the gut. However, its role in concomitant administration with commonly prescribed medications, including metformin (MET) and acarbose (ACR) for diabetes, is unclear. Therefore, this study assessed the effect of A. escu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…We found that okra treatment in pre-diabetic and T2D patients has beneficial effects on glycaemic control, as demonstrated by a significant reduction in the level of FBG. These findings are consistent with the results reported by previous researchers ( Khatun et al, 2011 ; Majd et al, 2018 ; Nguekouo et al, 2018 ; Husen et al, 2020 ; Uadia et al, 2020 ; Wu et al, 2020 ; Yan et al, 2020 ; Tyagita et al, 2021 ; Haque et al, 2022 ). One of the proposed mechanisms that okra targets in reducing FBG is the stimulation of hepatic glycogen synthesis and pancreatic islet regeneration, thus leading to increased insulin secretion and subsequent delay in the intestinal absorption of glucose.…”
Section: Discussionsupporting
confidence: 93%
“…We found that okra treatment in pre-diabetic and T2D patients has beneficial effects on glycaemic control, as demonstrated by a significant reduction in the level of FBG. These findings are consistent with the results reported by previous researchers ( Khatun et al, 2011 ; Majd et al, 2018 ; Nguekouo et al, 2018 ; Husen et al, 2020 ; Uadia et al, 2020 ; Wu et al, 2020 ; Yan et al, 2020 ; Tyagita et al, 2021 ; Haque et al, 2022 ). One of the proposed mechanisms that okra targets in reducing FBG is the stimulation of hepatic glycogen synthesis and pancreatic islet regeneration, thus leading to increased insulin secretion and subsequent delay in the intestinal absorption of glucose.…”
Section: Discussionsupporting
confidence: 93%
“…The use of plant-based active moieties shows significant benefits with required safety. Medicinal plants such as cruciferous vegetables, garlic, andrographolide are explored for the treatment of different disorders such as cancer (Akkol et al 2020 ; Aǧagündüz et al 2022 ; Mitra et al 2022 ), psychiatric and neurological disorders (Vieira et al 2020 ; Akkol et al 2020 ; Farooq et al 2021 ), thrombotic, inflammatory and nociceptive conditions (Khan et al 2020 ; Uddin Chy et al 2021 ), fibromyalgia (Ferrarini et al 2022 ), hyperglycemic and diabetic conditions (Mechchate et al 2021 ; Haque et al 2022 ), antidepressant, antidiarrheal and anxiolytic activity (Hossain et al 2021 ; Jahan et al 2022 ) and many other chronic disorders (Iqbal et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to this study, taking A. esculentus pod extract along with metformin and acarbose might decrease the efficiency of antidiabetic medications; as a result, concurrent consumption A. esculentus pod extract with conventional medications is not advised. 20…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…According to this study, taking A. esculentus pod extract along with metformin and acarbose might decrease the efficiency of antidiabetic medications; as a result, concurrent consumption A. esculentus pod extract with conventional medications is not advised. 20 Siddique et al evaluated the in vitro antidiabetic potential of A. esculentus methanolic extract, employing an inhibitory model for the enzymes a-amylase and a-glucosidase. At doses of 50-200 mg mL −1 , the percentage inhibition of a-glucosidase and aamylase ranged from 14.36 ± 0.099 to 19.23 ± 0.172% and 15.89 ± 1.877 to 37.19 ± 7.430%, respectively.…”
Section: Antidiabetic and Antihyperlipidemic Activitymentioning
confidence: 99%